2014
DOI: 10.1104/pp.114.246405
|View full text |Cite
|
Sign up to set email alerts
|

Transient Silencing of CHALCONE SYNTHASE during Fruit Ripening Modifies Tomato Epidermal Cells and Cuticle Properties    

Abstract: Tomato (Solanum lycopersicum) fruit ripening is accompanied by an increase in CHALCONE SYNTHASE (CHS) activity and flavonoid biosynthesis. Flavonoids accumulate in the cuticle, giving its characteristic orange color that contributes to the eventual red color of the ripe fruit. Using virus-induced gene silencing in fruits, we have down-regulated the expression of SlCHS during ripening and compared the cuticles derived from silenced and nonsilenced regions. Silenced regions showed a pink color due to the lack of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 70 publications
5
49
0
Order By: Relevance
“…polysaccharides, phenolics, and waxes) would explain the lower Young's modulus measured in TAGL1-repressed cuticles. This observation supports the results obtained in the cuticles of nor mutants and CHS-silenced tomatoes (Bargel and Neinhuis, 2004;España et al, 2014a).…”
Section: Tagl1 Regulates the Composition And Biomechanical Propertiessupporting
confidence: 92%
See 1 more Smart Citation
“…polysaccharides, phenolics, and waxes) would explain the lower Young's modulus measured in TAGL1-repressed cuticles. This observation supports the results obtained in the cuticles of nor mutants and CHS-silenced tomatoes (Bargel and Neinhuis, 2004;España et al, 2014a).…”
Section: Tagl1 Regulates the Composition And Biomechanical Propertiessupporting
confidence: 92%
“…Other transcription factors, such as SlMYB12 and NOR, have been shown to alter cuticle color during ripening due to a decrease in phenolics (Bargel and Neinhuis, 2004;Adato et al, 2009), but cuticle deposition was only affected by SlMYB12 (Adato et al, 2009). More recently, a significant decrease in cuticle and most of its components, except for waxes, was reported in tomato fruits silencing CHS during ripening (España et al, 2014a). The significant reduction in cuticle components known to confer stiffness (i.e.…”
Section: Tagl1 Regulates the Composition And Biomechanical Propertiesmentioning
confidence: 99%
“…One of the key steps of the flavonoid pathway in tomato fruit is the synthesis of naringenin chalcone from 4‐coumaroyl‐CoA, a reaction catalyzed by CHALCONE SYNTHASE (CHS; Muir et al ., ; Schijlen et al ., ). Two CHS genes ( CHS1 and CHS2 ) have been previously shown to be transcriptionally induced upon onset of fruit ripening (España et al ., ). Accordingly, abundance of these two proteins was induced in the fruit skin at the Br stage.…”
Section: Resultsmentioning
confidence: 97%
“…Recent results have indeed found that the fruit surface structure is influenced by cutin deposition; however, in this work, a change in cutin deposition was not necessarily shown to result in a change in epidermal cell shape (Petit et al, 2014). Furthermore, silencing of CHALCONE SYNTHASE expression (a gene responsible for the inclusion of naringenin chalcone in the tomato cuticle) results in a stiffer, less elastic cuticle surrounding flatter epidermal cells (Schijlen et al, 2007;España et al, 2014). These results hint at a potential dependence on the surrounding cuticle with regard to epidermal cell structure.…”
Section: Silencing Of Slmixta-like Results In the Flattening Of Epidementioning
confidence: 65%